Implementation of Good Corporate Governance in The Winning Company Asia Sustainability Reporting Rating (ASRRAT) 2023 - Breliastiti, Ririn; Temy Setiawan; Tiwi Herninta; Calvin Gouw; Jastin Jovanus; Bella Rosewita (Dinasti Publisher, 2024)
The evaluation of organizational structures and corporate governance practices within companies reveals opportunities for refinement and improvement. While most companies have comprehensive organizational structures, there is a need for optimization to enhance efficiency and effectiveness. Despite widespread adoption of GCG principles, implementation could be improved, emphasizing the importance of fortifying oversight mechanisms and transparency. Strengthening internal control systems is crucial for bolstering efficiency, effectiveness, and accountability in risk management and goal achievement. Additionally, companies honored with awards in ASRRAT 2023 have opportunities to enhance sustainability performance by identifying areas for improvement and strategizing for long-term sustainability goals. Collaborative efforts among companies to share knowledge and best practices in sustainability and corporate social responsibility can accelerate progress in these areas.